Bipyridine type Co-complexes as hole-transporting material dopants in perovskite solar cells. Issue 21 (10th February 2016) - Ye, Jiajiu; Zhou, Li; Zhu, Liangzheng; Zhang, Xuhui; Shao, Zhipeng; Pan, Xu; Dai, Songyan
Abstract : This work focuses on preparing a series of substituted bipyridine cobalt complexes as HTM dopants using a co-solvent of dichloroethane and acetylacetone as the HTM solvent, achieving an optimal power conversion efficiency of 14.91%. Abstract : Hole-transporting materials (HTM) have significant effects on solar cell properties and cobalt complexes are commonly used as dopants in the HTM layer. The molecular structure of the ligands always has an important influence on the capability of the dopant. In this work, a series of substituted bipyridine cobalt complexes were synthesized by modification of the molecular structure and were investigated as possible dopant alternatives. Their electron conductive ability and redox potentials were tested by characterizing their absorption spectroscopy and conductivity properties. The best dopant, based on tris(4, 4′-di- tert -butyl-2, 2′-dipyridyl)-cobalt(iii ) tris[bis(trifluoromethylsulfonyl)-imide], resulted in a power conversion efficiency of up to 14.91% measured under standard solar conditions (AM 1.5G, 100 mW cm −2 ). In addition, the co-solvent system of dichloroethane and acetylacetone was specifically selected for the bipyridine type dopants due to the greater solubility of both spiro and the dopant in this system. Because of the easy acquisition of the ligand and the simplicity of the synthesis of the complexes, this dopant represents a practical alternative as an efficient dopant for hole-transporting materials in perovskite solar cells.